Reversible ethambutol-induced optic neuropathy: report of a rare case - Syntia Nusanti; Rasyidia Laksmita Putri; Dearaini Dearaini (Universa Medicina, 2022)
BackgroundEthambutol (EMB) is one of the first-line anti-tuberculosis therapy. One of its precarious side effects is ethambutol-induced optic neuropathy (EON). The ocular manifestations of EON include painless loss of central vision and cecocentral scotomas in the visual field. Case DescriptionA 60-year old man presented with gradual and painless visual loss since 3 months prior to visit. The accompanying symptoms were frequent headache without double vision and photophobia. He had been diagnosed with pulmonary tuberculosis (TB) for 9 months and consumed EMB for 7 months before being advised to discontinue. There was neither history of systemic diseases nor family history of neuropathy. Examination showed reduced visual acuity with positive relative afferent pupillary defect (RAPD) on right eye. Humphrey test showed bilateral generalized visual loss. Ocular computed tomography (OCT) showed retinal nerve fiber layer (RNFL) thickness was within normal limit. Magnetic resonance Imaging (MRI) brain indicated unremarkable result for optic neuropathy. Based on the examinations listed above, this patient was diagnosed as EON and EMB was stopped immediately. Patient was given oral citicoline 1000mg and zinc supplementation for one month. After 1 st and 3 rd month follow up, patient’s visual function was gradually improved. The ophthalmic examinations indicated recovery of the visual function. ConclusionsThis case suggested that an early detection and intervention in patient with EON has promising result in visual outcome. EON is a reversible optic neuropathy if the ocular toxicity is monitored closely among the tuberculosis patients who are prescribed EMB regiment.